1 MODE OF DELIVERY, SIZE FOR GESTATIONAL AGE, AND LOW APGAR SCORES IN VERTEX PRETERM INFANTS. Issue 1 (1st January 2007) - Lee, H. C.; Gould, J. B.
Abstract : Purpose: Decreased mortality has been observed with cesarean delivery (CD) for small for gestational age (SGA) as opposed to appropriate for gestational age (AGA) preterm vertex infants. To assess perinatal morbidity, we compared gestational age (GA)-specific 5-minute Apgar scores between SGA and AGA infants according to mode of delivery, using a national cohort database. Methods: We analyzed the National Center for Health Statistics US linked birth/death records, 1997-2001, for 1, 033, 944 vertex singleton live births at 26 to 36 weeks GA born to mothers without previous CD. Infants were considered SGA (< 10%ile) or AGA (10-90%ile) based on reported birth weight percentiles. The rates of 5-minute Apgar scores < 4 were compared according to mode of delivery for SGA and AGA. Relative risks (RRs) along with 95% confidence intervals were computed. Results: The incidence of low Apgar decreased with increasing GA (10.6-0.2%). At all GAs, low Apgar was markedly higher in SGA (38.4-0.5%) than AGA infants (7.2-0.2%). For AGA, vaginal delivery was associated with lower rates of Apgar < 4 than CD. For SGA, vaginal delivery compared to CD was associated with a 2 to 4 times higher percentage of Apgar < 4 at 26 to 32 weeks GA. This morbidity difference was lost at 33 weeks GA (Table 1 ). Conclusions: Large numbers of SGA preterm infants have 5-minute Apgar < 4. At 26 to 32 weeks, Apgar < 4 was more prevalent in SGA vertex infants delivered vaginally compared to CD. Scores < 4 were not reduced in AGA infants born by CD. These morbidity findings mirror those previously reported for mortality. We speculate that SGA infants at 26 to 32 weeks, who may have been in an environment of placental insufficiency, may benefit from avoiding labor and undergoing CD.